2022
DOI: 10.3389/fonc.2022.960005
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-based reclassification and risk stratification of skull-base chordomas

Abstract: BackgroundSkull-base chordomas are rare malignant bone cancers originating from the remnant of the notochord. Survival is variable, and clinical or molecular factors cannot reliably predict their outcomes. This study therefore identified epigenetic subtypes that defined new chordoma epigenetic profiles and their corresponding characteristics.MethodsMethylation profiles of 46 chordoma-resected neoplasms between 2008 and 2014, along with clinical information, were collected. K-means consensus clustering and prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 52 publications
1
20
1
Order By: Relevance
“…Conversely, recurrent chordomas showed an enrichment of Treg cells (Foxp3) and natural killer (NK) cells (CD56) (Figure S6). 30 Despite the elevated proportion of Tregs observed in recurrent chordomas (Figure S5), the cells exhibited significant expression of TIGHT, CTLA4, PDCD1, ENTPD1 and HAVCR2 (Figure 2B), indicating the immunosuppressive nature of Tregs. One of the primary ways in which chordoma lesions exhibit immunosuppression is through the identification of CTLA4 and PDCD1 expression on Tregs 31,32 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Conversely, recurrent chordomas showed an enrichment of Treg cells (Foxp3) and natural killer (NK) cells (CD56) (Figure S6). 30 Despite the elevated proportion of Tregs observed in recurrent chordomas (Figure S5), the cells exhibited significant expression of TIGHT, CTLA4, PDCD1, ENTPD1 and HAVCR2 (Figure 2B), indicating the immunosuppressive nature of Tregs. One of the primary ways in which chordoma lesions exhibit immunosuppression is through the identification of CTLA4 and PDCD1 expression on Tregs 31,32 .…”
Section: Resultsmentioning
confidence: 94%
“…We found that FAP (a fibroblast marker) has higher expression in recurrent chordoma, and this result was confirmed by IHC experiments (Figures S16 and S17). 30 Using specific markers, a total of 1796 fibroblasts were identified, which were classified into four distinct subclusters by U‐map analysis (Figures 4A and S18 and Table S6). Confirming their identity as fibroblasts, all four subclusters demonstrated elevated expression levels of well‐known fibroblast markers including DCN, LUM and COL1A2 8,29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focused on methylation and RNA sequencing have identified groups of patients with either an inflamed or non-inflamed phenotype and associated these groups to clinical outcome, all with varying implications. 34–36 For instance, Zuccato et al found through methylation profiling that a group of patients presenting an inflamed phenotype had a worse prognosis than patients without these inflammatory features, 35 whereas Huo et al observed that patients from the non-inflamed group had a worse clinical outcome. 34 Furthermore, Baluszcek et al described two similar groups based on methylation and transcriptomic profiling, without finding an association between these groups and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focussed on methylation and RNA sequencing have identified groups of patients with either an inflamed or non-inflamed phenotype and associated these groups to clinical outcome, all with varying implications 2931 . For instance, Zuccato et al found through methylation profiling that a group of patients presenting an inflamed phenotype had a worse prognosis than patients without these inflammatory features 30 , whereas Huo et al observed that patients from the non-inflamed group had a worse clinical outcome 29 . Furthermore, Baluszcek et al described two similar groups based on methylation and transcriptomic profiling, without finding an association between these groups and survival 31 .…”
Section: Discussionmentioning
confidence: 99%